A SiC whisker toughened alumina ceramic tool and preparation method thereof

By adding SiC whiskers and toughening auxiliary powder to the alumina ceramics, combined with sintering and oscillation sintering processes, the problems of high brittleness and densification of alumina ceramics are solved, and the high density and fracture toughness of the ceramics are achieved.

CN119143515BActive Publication Date: 2025-03-21LAIWU HEYUAN CERAMIC TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411321925.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-03-21
Estimated Expiration
2044-09-23

AI Technical Summary

Technical Problem

Alumina ceramics have problems such as high brittleness and low fracture toughness, and the presence of silicon carbide whiskers will hinder the densification of the ceramics, resulting in limited space for improving toughness.

Method used

SiC whisker toughened alumina ceramic tool is used to improve the density and fracture toughness of the ceramic by adding silicon carbide whiskers and toughened auxiliary powders to the alumina ceramic powder, including iloxane slag, chromium trioxide and zirconia.

Benefits of technology

It effectively improves the density and fracture toughness of alumina ceramics, overcomes the problem of hindering densification of silicon carbide whiskers, and significantly improves the mechanical properties of the ceramics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present application relates to the technical field of ceramic tools, and more specifically, it relates to a SiC whisker toughened alumina ceramic tool and a preparation method thereof. A SiC whisker toughened alumina ceramic tool, the SiC whisker toughened alumina ceramic tool is composed of alumina ceramic powder, silicon carbide whiskers and toughening auxiliary powder; the toughening auxiliary powder includes the following raw materials in parts by weight: 20-30 parts of ferro-titanium slag and 6-10 parts of chromium trioxide. The SiC whisker toughened alumina ceramic tool of the present application has a dense structure and has better fracture toughness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of ceramic cutting tools, and more specifically, to a SiC whisker toughened alumina ceramic cutting tool and a preparation method thereof. Background Art

[0002] Alumina ceramics are an important engineering ceramic material with excellent physical and chemical properties such as high hardness, high melting point, wear resistance, corrosion resistance, high dielectric strength, high dielectric constant, and low dielectric loss. It is widely used in machinery, chemical industry, electronics, metallurgy, aerospace and other fields.

[0003] However, alumina ceramics have the defects of high brittleness and low fracture toughness, so how to improve the toughness of alumina ceramics is one of the main research directions of this material. Silicon carbide whiskers are a single crystal with a diameter of nanometers to micrometers and a high degree of orientation. When silicon carbide whiskers are added to alumina ceramics, they will toughen the alumina ceramics through the pull-out connection mechanism and the crack deflection mechanism, thereby effectively improving the brittleness of alumina ceramics and improving their fracture toughness.

[0004] However, the presence of silicon carbide whiskers will hinder the densification of alumina ceramics during the sintering process. When the ceramic matrix shrinks, circumferential tensile stress and radial tensile stress will be formed around the silicon carbide whiskers, thereby hindering the shrinkage and deformation of the ceramic matrix, resulting in difficulties in the densification of alumina ceramics. At the same time, the toughness of alumina ceramics still has room for improvement. Summary of the invention

[0005] In order to overcome the defects that the density and toughness of silicon carbide whisker toughened alumina ceramics are still insufficient, the present application provides a SiC whisker toughened alumina ceramic tool and a preparation method thereof.

[0006] In the first aspect, the present application provides a SiC whisker toughened alumina ceramic tool, which adopts the following technical solution:

[0007] A SiC whisker toughened alumina ceramic tool, the SiC whisker toughened alumina ceramic tool comprising alumina ceramic powder, silicon carbide whiskers and toughening auxiliary powder;

[0008] The toughening auxiliary powder comprises the following raw materials in parts by weight: 20-30 parts of ferrotitanium slag and 6-10 parts of chromium trioxide.

[0009] Ferro-titanium slag contains high contents of alumina, calcium oxide, titanium dioxide and other substances, and its ratio meets the requirements of mineral phase synthesis of calcium hexaaluminate. Calcium hexaaluminate is a high-temperature aluminate compound of the calcium oxide-alumina system, and its thermal expansion coefficient is very close to that of alumina and chromium trioxide. Therefore, the three have good matching during sintering.

[0010] Among them, calcium hexaaluminate grains can form a long plate morphology with a large aspect ratio during the growth process, so that crack deflection, crack bridging and grain pullout can be formed during the expansion process, thereby obtaining an extremely good toughening effect. Chromium trioxide and aluminum oxide both have the same hexagonal close-packed structure, so chromium ions can easily occupy the octahedral voids in the aluminum trioxide crystal structure and form an aluminum-chromium solid solution, which has the effect of small particles and dense structure, thereby effectively improving the density of alumina ceramics.

[0011] Preferably, the toughening auxiliary powder also includes zirconium oxide.

[0012] When zirconium oxide is added to the toughening auxiliary powder, zirconium oxide will synergize with titanium dioxide in the titanium ferro-slag to effectively increase the crack propagation resistance, thereby further improving the fracture toughness of the alumina ceramic.

[0013] Preferably, the mass ratio of the ferro-titanium slag to the zirconium oxide is (20-30): (2-4).

[0014] When the titanium ferro slag and zirconium oxide are in the above mass ratio, zirconium oxide will achieve a more prominent synergistic effect with titanium dioxide in the titanium ferro slag, thereby significantly improving the fracture toughness of alumina ceramics.

[0015] Preferably, the auxiliary toughening powder further comprises magnesium oxide;

[0016] and / or;

[0017] Lanthanum trioxide.

[0018] Preferably, the auxiliary toughening powder also includes magnesium oxide and lanthanum trioxide.

[0019] The addition of ferrotitanium slag can promote the low-temperature dense sintering of ceramics, but the calcium oxide in the ferrotitanium slag can easily form a liquid film, causing abnormal grain growth. The addition of magnesium oxide can change the anisotropic liquid-solid interface energy, thereby reducing the boundary free energy, thereby inhibiting the abnormal growth of grains and contributing to the homogenization of the ceramic structure.

[0020] However, the addition of magnesium oxide will also promote the growth of alumina grains, which is not conducive to the formation of nano-scale fine grains, while lanthanum trioxide is difficult to form a solid solution with alumina. It will continue to exist on the alumina grain boundaries, hindering ion migration, thereby reducing the grain boundary migration rate and inhibiting grain growth. However, lanthanum trioxide will also inhibit the transformation of alumina grains, which is not conducive to low-temperature sintering, and thus affects the density of alumina ceramics.

[0021] When magnesium oxide and lanthanum trioxide are used together, a synergistic effect will occur, in which lanthanum trioxide hinders the growth of alumina grains, while magnesium oxide promotes low-temperature dense sintering of ceramics and inhibits abnormal grain growth, thereby achieving a denser structure and more uniform grains of alumina ceramics, exhibiting better fracture toughness.

[0022] Preferably, the mass ratio of the magnesium oxide to the lanthanum trioxide is (1-2): (1-2).

[0023] When magnesium oxide and lanthanum trioxide adopt the above mass ratio, the structure of the prepared alumina ceramic will be denser and have better fracture toughness.

[0024] Preferably, the toughening auxiliary powder comprises the following raw materials in parts by weight: 20-30 parts of ferrotitanium slag, 6-10 parts of chromium trioxide, 2-4 parts of zirconium oxide, 2-4 parts of magnesium oxide and 2-4 parts of lanthanum trioxide.

[0025] Preferably, the SiC whisker toughened alumina ceramic cutting tool comprises the following raw materials: 70-80 parts of alumina ceramic powder, 10-20 parts of silicon carbide whiskers and 5-15 parts of toughening auxiliary powder.

[0026] In a second aspect, the present application provides a method for preparing a SiC whisker toughened alumina ceramic tool, using the following technical solution:

[0027] A method for preparing a SiC whisker toughened alumina ceramic tool comprises the following steps:

[0028] S1. Firstly, alumina ceramic powder, silicon carbide whiskers and toughening auxiliary powder are dispersed in ethanol, and then rotary evaporated, ground and sieved to obtain ceramic mixed powder;

[0029] S2, loading the ceramic mixed powder into a graphite mold, and performing spark plasma sintering, the sintering temperature is 900-1800° C., the holding time is 10-20 min, the sintering pressure is 40-100 MPa, and after the sintering is completed, it is cooled to room temperature, and then ground and polished to obtain a pretreated SiC whisker toughened alumina ceramic tool;

[0030] S3. Place the pretreated SiC whisker toughened alumina ceramic tool between two graphite pressure heads and place it in an oscillating sintering furnace. First, heat it to 1650-1800°C, pressurize it to 80-120MPa at a rate of 2-8KN / min, apply a median pressure of 80-120MPa, an amplitude of 5-30MPa, a frequency of 10-20Hz, and keep it warm for 20-30min. After the holding time is over, stop the oscillation force and reduce the pressure to 1-5MPa. Then, cool the temperature to 1400-1600°C, apply a median pressure of 100-300MPa, an amplitude of 5-30MPa, a frequency of 10-20Hz, and keep it warm for 1-3h. After the holding time is over, stop the oscillation force and cool it to room temperature to obtain a SiC whisker toughened alumina ceramic tool.

[0031] In summary, this application has the following beneficial effects:

[0032] 1. Titanium ferro-slag contains high content of alumina, calcium oxide and titanium dioxide, and its ratio meets the mineral phase synthesis requirements of calcium hexaaluminate. Calcium hexaaluminate is a high-temperature aluminate compound of calcium oxide-alumina system, and its thermal expansion coefficient is very close to that of alumina and chromium trioxide. Therefore, the three have good matching properties during sintering;

[0033] Among them, calcium hexaaluminate grains can form a long plate morphology with a large aspect ratio during the growth process, so that crack deflection, crack bridging and grain pullout can be formed during the expansion process, thereby obtaining an extremely good toughening effect. Chromium trioxide and aluminum oxide both have the same hexagonal close-packed structure, so chromium ions can easily occupy the octahedral voids in the aluminum trioxide crystal structure and form an aluminum-chromium solid solution, which has the effect of small particles and dense structure, thereby effectively improving the density of alumina ceramics.

[0034] 2. When zirconium oxide is added to the toughening auxiliary powder, zirconium oxide will synergize with titanium dioxide in the titanium ferro-slag, effectively increasing the crack propagation resistance, thereby further improving the fracture toughness of alumina ceramics.

[0035] 3. The addition of ferrotitanium slag can promote the low-temperature dense sintering of ceramics, but the calcium oxide in the ferrotitanium slag can easily form a liquid phase film, which causes abnormal growth of grains. The addition of magnesium oxide can change the anisotropic liquid-solid interface energy, thereby reducing the boundary free energy, thereby inhibiting the abnormal growth of grains and contributing to the homogenization of the ceramic structure.

[0036] However, the addition of magnesium oxide will also promote the growth of alumina grains, which is not conducive to the formation of nano-scale fine grains, while lanthanum trioxide is difficult to form a solid solution with alumina. It will continue to exist on the alumina grain boundary, hindering ion migration, thereby reducing the grain boundary migration rate and inhibiting grain growth. However, lanthanum trioxide will also inhibit the transformation of alumina grains, which is not conducive to low-temperature sintering, and thus affects the density of alumina ceramics;

[0037] When magnesium oxide and lanthanum trioxide are used together, a synergistic effect will occur, in which lanthanum trioxide hinders the growth of alumina grains, while magnesium oxide promotes low-temperature dense sintering of ceramics and inhibits abnormal grain growth, thereby achieving a denser structure and more uniform grains of alumina ceramics, exhibiting better fracture toughness. DETAILED DESCRIPTION

[0038] The present application is further described in detail below in conjunction with Comparative Example 1 of Examples 1-13.

[0039] raw material

[0040] Alumina ceramic powder Hebei Yuechao wear-resistant materials; Silicon carbide whisker Ningbo Luofei Nanotechnology; Titanium ferro slag Anyang Xinze Metallurgical Refractory Materials; Chromium trioxide CAS: 1308-38-9; Zirconium oxide CAS: 1314-23-4; Magnesium oxide CAS: 1309-48-4; Lanthanum trioxide CAS: 1312-81-8; Ethanol CAS: 64-17-5.

[0041] Example

[0042] Example 1

[0043] A SiC whisker toughened alumina ceramic tool is made of 75g alumina ceramic powder, 15g silicon carbide whiskers and 10g toughening auxiliary powder; wherein the toughening auxiliary powder is composed of ferrotitanium slag and chromium trioxide, and the mass ratio of ferrotitanium slag to chromium trioxide is 25:8.

[0044] A SiC whisker toughened alumina ceramic tool comprises the following steps:

[0045] S1. Firstly, alumina ceramic powder, silicon carbide whiskers and toughening auxiliary powder are dispersed in ethanol, and then rotary evaporated, ground and sieved to obtain ceramic mixed powder;

[0046] S2, loading the ceramic mixed powder into a graphite mold, and performing spark plasma sintering at a sintering temperature of 1200° C., a holding time of 15 min, and a sintering pressure of 60 MPa. After sintering, the mixed powder is cooled to room temperature, and then ground and polished to obtain a pretreated SiC whisker toughened alumina ceramic tool;

[0047] S3. Place the pretreated SiC whisker toughened alumina ceramic tool between two graphite pressure heads and place it in an oscillating sintering furnace. First, heat it to 1700°C, pressurize it to 100MPa at a rate of 5KN / min, apply a median pressure of 100MPa, an amplitude of 20MPa, a frequency of 15Hz, and keep it warm for 25min. After the holding time is over, stop the oscillation force and reduce the pressure to 2MPa. Then, cool the temperature to 1500°C, apply a median pressure of 200MPa, an amplitude of 20MPa, a frequency of 15Hz, and keep it warm for 2h. After the holding time is over, stop the oscillation force and cool it to room temperature to obtain a SiC whisker toughened alumina ceramic tool.

[0048] Example 2

[0049] The difference from Example 1 is that the toughening auxiliary powder also includes zirconium oxide, and the mass ratio of titanium iron slag to zirconium oxide is 25:3.

[0050] Embodiment 3-4

[0051] The difference from Example 1 is that the mass ratio of ferrotitanium slag to zirconium oxide is different, as shown in Table 1.

[0052] Table 1 Mass ratio of ferrotitanium slag to zirconium oxide in Examples 2-4

[0053]

[0054] Example 5

[0055] The difference from Example 2 is that the toughening auxiliary powder also includes magnesium oxide, and the mass ratio of ferrotitanium slag to magnesium oxide is 25:6.

[0056] Example 6

[0057] The difference from Example 2 is that the toughening auxiliary powder also includes lanthanum trioxide, and the mass ratio of ferrotitanium slag to lanthanum trioxide is 25:6.

[0058] Example 7

[0059] The difference from Example 2 is that the toughening auxiliary powder also includes magnesium oxide and lanthanum trioxide, and the mass ratio of ferrotitanium slag, magnesium oxide and lanthanum trioxide is 25:3:3.

[0060] Embodiment 8-9

[0061] The difference from Example 7 is that the mass ratio of magnesium oxide to lanthanum trioxide is different, as shown in Table 2.

[0062] Table 2 The mass ratio of magnesium oxide and lanthanum trioxide in Examples 7-9

[0063]

[0064] Embodiment 10-11

[0065] The difference from Example 7 is that the mass proportions of the components of the auxiliary toughening powder are different, as shown in Table 3.

[0066] Table 3 Mass ratio of each component of auxiliary toughening powder of Example 7 and Examples 10-11

[0067]

[0068] Examples 12-13

[0069] The difference from Example 7 is that the addition amounts of the components of the SiC whisker toughened alumina ceramic tool are different, as shown in Table 4.

[0070] Table 4 Addition amount of each component of SiC whisker toughened alumina ceramic cutting tools in Examples 7, 12-13 / g

[0071]

[0072] Comparative Example

[0073] Comparative Example 1

[0074] The difference from Example 1 is that no toughening auxiliary powder is added.

[0075] Performance testing

[0076] Detection Methods

[0077] 1. Density detection

[0078] Three samples were taken from Examples 1-13 respectively, and the sample size was 25 mm×3.4 mm×4.8 mm. The density of the samples was then tested by the Archimedes displacement method. The density formula is: density = mass / displacement. The test data were averaged. The test data are shown in Table 5.

[0079] 2. Fracture toughness test

[0080] Three samples were taken from Examples 1-13 respectively, with a sample size of 25 mm × 3.4 mm × 4.8 mm. The fracture toughness of the samples was then tested with reference to GB / T23806-2009 “Fine Ceramics Fracture Toughness Test Method - Single-Sided Pre-cracked Beam Method”. The test data were averaged and the data are shown in Table 5.

[0081] Table 5 Test data table of Examples 1-13 and Comparative Example 1

[0082]

[0083] Referring to Example 1 and Comparative Example 1 and in combination with Table 5, it can be seen that the density and fracture toughness of Example 1 are significantly enhanced compared with those of Comparative Example 1, which indicates that adding toughening auxiliary powder to silicon carbide whisker toughened alumina ceramics can effectively improve its density and fracture toughness.

[0084] The reason is that ferro-titanium slag contains high content of alumina, calcium oxide and titanium dioxide, and its ratio meets the mineral phase synthesis requirements of calcium hexaaluminate. Calcium hexaaluminate is a high-temperature aluminate compound of the calcium oxide-alumina system, and its thermal expansion coefficient is very close to that of alumina and chromium trioxide. Therefore, the three have good matching properties during sintering.

[0085] Among them, calcium hexaaluminate grains can form a long plate morphology with a large aspect ratio during the growth process, so that crack deflection, crack bridging and grain pullout can be formed during the expansion process, thereby obtaining an extremely good toughening effect. Chromium trioxide and aluminum oxide both have the same hexagonal close-packed structure, so chromium ions can easily occupy the octahedral voids in the aluminum trioxide crystal structure and form an aluminum-chromium solid solution, which has the effect of small particles and dense structure, thereby effectively improving the density of alumina ceramics.

[0086] In addition, the first stage of the silicon carbide whisker toughened alumina ceramics of the present application is carried out under high temperature conditions. Under the application of appropriate oscillating force and in a short period of time, uniform deformation and a large number of defects and dislocations will occur inside the material, avoiding the pores caused by the deformation mechanism not keeping up with the deformation rate, and avoiding excessive grain growth, so as to achieve rapid densification of the material and high-strength grain boundaries, and minimize defects.

[0087] The second stage is carried out at a slightly lower temperature, with appropriate oscillation force applied to avoid excessive grain growth. Long-term forging can ensure that the grain size increases slowly. Under the premise of ensuring a low grain size, it can promote the movement of dislocations and defects, causing the material to harden. At the same time, the material will further deform, causing the whiskers to further align, achieving further increases in the material's dislocation density and grain boundary strength, thereby improving the material's mechanical properties. The two stages work together to effectively overcome the stress generated around the silicon carbide whiskers during contraction and deformation, and achieve directional alignment of the silicon carbide whiskers in the composite material, greatly improving the mechanical properties of the composite material.

[0088] Referring to Example 1 and Example 2 and combining with Table 5, it can be seen that compared with Example 1, the density and fracture toughness of Example 2 are significantly improved, which shows that the addition of zirconium oxide can effectively improve the density and fracture toughness of silicon carbide whisker toughened alumina ceramics.

[0089] The reason is that when zirconium oxide is added to the toughening auxiliary powder, zirconium oxide will synergize with titanium dioxide in the titanium ferro-slag, effectively increasing the resistance to crack propagation, thereby further improving the fracture toughness of the alumina ceramic.

[0090] Referring to Examples 2-4 and in combination with Table 5, it can be seen that the fracture toughness of Examples 3-4 is slightly reduced compared to that of Example 2, which indicates that when zirconium oxide is added in the amount of Example 2, the prepared silicon carbide whisker toughened alumina ceramic will have better fracture toughness.

[0091] With reference to Example 2 and Examples 5-7 and in combination with Table 5, it can be seen that, relative to Example 2, the density of Example 5 is significantly improved, but the fracture toughness of Example 5 is slightly decreased; the fracture toughness of Example 6 is significantly improved, but the density of Example 6 is slightly decreased; both the density and fracture toughness of Example 7 are significantly improved, and the degree of improvement is similar to that of Examples 5-6.

[0092] This shows that the addition of magnesium oxide can improve the density of silicon carbide whisker toughened alumina ceramics, and the addition of lanthanum trioxide can improve the fracture toughness of silicon carbide whisker toughened alumina ceramics. After adding magnesium oxide and lanthanum trioxide together, the prepared silicon carbide whisker toughened alumina ceramics will have better density and fracture toughness.

[0093] The reason is that the addition of ferrotitanium slag can promote the low-temperature dense sintering of ceramics, but the calcium oxide in the ferrotitanium slag can easily form a liquid phase film, which causes abnormal growth of grains, while the addition of magnesium oxide can change the anisotropic liquid-solid interface energy, thereby reducing the boundary free energy, thereby inhibiting the abnormal growth of grains and contributing to the homogenization of the ceramic structure.

[0094] However, the addition of magnesium oxide will also promote the growth of alumina grains, which is not conducive to the formation of nano-scale fine grains, while lanthanum trioxide is difficult to form a solid solution with alumina. It will continue to exist on the alumina grain boundary, hindering ion migration, thereby reducing the grain boundary migration rate and inhibiting grain growth. However, lanthanum trioxide will also inhibit the transformation of alumina grains, which is not conducive to low-temperature sintering, and thus affects the density of alumina ceramics;

[0095] When magnesium oxide and lanthanum trioxide are used together, a synergistic effect will occur, in which lanthanum trioxide hinders the growth of alumina grains, while magnesium oxide promotes low-temperature dense sintering of ceramics and inhibits abnormal grain growth, thereby achieving a denser structure and more uniform grains of alumina ceramics, exhibiting better fracture toughness.

[0096] With reference to Examples 7-9 and in combination with Table 5, it can be seen that, relative to Example 7, the density of Example 8 is significantly decreased, but the fracture toughness of Example 8 is significantly improved; the density of Example 9 remains basically unchanged, but the fracture toughness is significantly decreased. This indicates that when the mass ratio of magnesium oxide to lanthanum trioxide is adopted in Examples 7-8, the prepared silicon carbide whisker toughened alumina ceramic will have both better density and fracture toughness.

[0097] With reference to Example 7 and Examples 10-11 and in combination with Table 5, it can be seen that, relative to Example 7, the density and fracture toughness of Examples 10-11 are significantly reduced. This indicates that when the components of the auxiliary toughening powder adopt the mass proportion of Example 7, the prepared silicon carbide whisker toughened alumina ceramic will have both better density and fracture toughness.

[0098] With reference to Example 7 and Examples 12-13 and in combination with Table 5, it can be seen that, relative to Example 7, the density and fracture toughness of Examples 12-13 are significantly reduced, which indicates that when the components of the SiC whisker toughened alumina ceramic tool adopt the mass proportion of Example 7, the prepared silicon carbide whisker toughened alumina ceramic will have both better density and fracture toughness.

[0099] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A SiC whisker toughened alumina ceramic tool, characterized in that: The SiC whisker toughened alumina ceramic tool is composed of alumina ceramic powder, silicon carbide whiskers and toughening auxiliary powder; The auxiliary toughening powder comprises the following raw materials in parts by weight: 20-30 parts of ferro-titanium slag and 6-10 parts of chromium trioxide; the auxiliary toughening powder also comprises magnesium oxide and lanthanum trioxide.

2. The SiC whisker toughened alumina ceramic tool according to claim 1, characterized in that: The toughening auxiliary powder also includes zirconium oxide.

3. The SiC whisker toughened alumina ceramic tool according to claim 2, characterized in that: The mass ratio of the titanium ferro slag to the zirconium oxide is (20-30): (2-4).

4. The SiC whisker toughened alumina ceramic tool according to claim 1, characterized in that: The mass ratio of the magnesium oxide to the lanthanum trioxide is (1-2): (1-2).

5. The SiC whisker toughened alumina ceramic tool according to claim 4, characterized in that: The toughening auxiliary powder comprises the following raw materials in parts by weight: 20-30 parts of ferro-titanium slag, 6-10 parts of chromium trioxide, 2-4 parts of zirconium oxide, 2-4 parts of magnesium oxide and 2-4 parts of lanthanum trioxide.

6. The SiC whisker toughened alumina ceramic tool according to claim 4, characterized in that: The SiC whisker toughened alumina ceramic tool comprises the following raw materials: 70-80 parts of alumina ceramic powder, 10-20 parts of silicon carbide whiskers and 5-15 parts of toughening auxiliary powder.

7. A SiC whisker toughened alumina ceramic tool according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1. Firstly, alumina ceramic powder, silicon carbide whiskers and toughening auxiliary powder are dispersed in ethanol, and then rotary evaporated, ground and sieved to obtain ceramic mixed powder; S2, loading the ceramic mixed powder into a graphite mold, and performing spark plasma sintering, the sintering temperature is 900-1800° C., the holding time is 10-20 min, the sintering pressure is 40-100 MPa, and after the sintering is completed, it is cooled to room temperature, and then ground and polished to obtain a pretreated SiC whisker toughened alumina ceramic tool; S3. Place the pretreated SiC whisker toughened alumina ceramic tool between two graphite pressure heads and place it in an oscillating sintering furnace. First, heat it to 1650-1800°C, pressurize it to 80-120MPa at a rate of 2-8KN / min, apply a median pressure of 80-120MPa, an amplitude of 5-30MPa, a frequency of 10-20Hz, and keep it warm for 20-30min. After the holding time is over, stop the oscillation force and reduce the pressure to 1-5MPa. Then, cool the temperature to 1400-1600°C, apply a median pressure of 100-300MPa, an amplitude of 5-30MPa, a frequency of 10-20Hz, and keep it warm for 1-3h. After the holding time is over, stop the oscillation force and cool it to room temperature to obtain a SiC whisker toughened alumina ceramic tool.

Citation Information

Patent Citations

  • Preparation method of compact calcium hexaluminate-corundum composite ceramic

    CN112125651A

  • Preparation method of SiC whisker toughened alumina ceramic cutter material

    CN114956846A